Nurturing the future: How positive parenting is related to children's skills and well-being - Laura Breitkopf; Shyamal Chowdhury; Shambhavi Priyam; Hannah Schildberg-Hörisch; Matthias Sutter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2024)
We study the relationship between parenting style and a broad range of children's skills and outcomes. Based on survey and experimental data from 5,580 children and their parents, we find that children exposed to positive parenting have higher IQs, are more altruistic, open to new experiences, conscientious, and agreeable, have a higher locus of control, self-control, and self-esteem, perform better in scholarly achievement tests, behave more prosocially in everyday life, and are more satisfied with their life. Positive parenting is negatively associated with children's neuroticism, patience, engagement in risky behaviors, and their emotional and behavioral problems.
Keywords: C91; D01; D10; 330; parenting style; child outcomes; economic preferences; personality traits; IQ